Proteasome inhibition reduces plasma cell and antibody secretion, but not angiotensin II-induced hypertension - Figueiredo Galvao, Hericka Bruna; Dinh, Quynh Nhu; Thomas, Jordyn M.; Wassef, Flavia; Diep, Henry; Bobik, Alex; Sobey, Christopher G.; Drummond, Grant R.; Vinh, Antony (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Depletion of mature B cells affords protection against experimental hypertension. However, whether B cell-mediated hypertension is dependent on differentiation into antibody-secreting cells (ASCs) remains unclear. Using the proteasome inhibitor, bortezomib, the present study tested the effect of ASC reduction on angiotensin II-induced hypertension. Methods: Male C57BL6/J mice were infused with angiotensin II (0.7 mg/kg/day; s.c.) for 28 days via osmotic minipump to induce hypertension. Normotensive control mice received saline infusion. Bortezomib (750 g/kg) or vehicle (0.1% DMSO) was administered (i.v.) 3 days prior to minipump implantation, and twice weekly thereafter. Systolic blood pressure was measured weekly using tail-cuff plethysmography. Spleen and bone marrow B1 (CD19+B220-), B2 (B220+CD19+) and ASCs (CD138hiSca-1+Blimp-1+) were enumerated by flow cytometry. Serum immunoglobulins were quantified using a bead-based immunoassay. Results: Bortezomib treatment reduced splenic ASCs by ~68% and ~64% compared to vehicle treatment in normotensive (2.00±0.30 vs 0.64±0.15 x105 cells; n=10-11) and hypertensive mice (0.52±0.11 vs 0.14±0.02 x105 cells; n=9-11), respectively. Bone marrow ASCs were also reduced by bortezomib in both normotensive (4.75±1.53 vs 1.71±0.41 x103 cells; n=9-11) and hypertensive mice (4.12±0.82 vs 0.89±0.18 x103 cells; n=9-11). Consistent with ASC reductions, bortezomib reduced serum IgM and IgG2a in all mice. Despite these reductions in ASCs and antibody levels, bortezomib did not affect angiotensin II-induced hypertension over 28 days (vehicle:182±4 mmHg vs bortezomib: 177±7 mmHg; n=9-11). Conclusion: Reductions in ASCs and circulating IgG2a and IgM did not ameliorate experimental hypertension, suggesting other immunoglobulin isotypes or B cell effector functions may promote angiotensin-II induced hypertension.